Totally tubeless, tubeless, and tubed percutaneous nephrolithotomy for treating kidney stones - Wilhelm, Konrad; Hein, Simon; Kunath, Frank; Schoenthaler, Martin; Schmidt, Stefanie (Cohrane Library, 2023)
Background: Percutaneous nephrolithotomy (PNL) is the standard of care for removing large kidney stones (> 2 cm). Once the procedure is complete, different exiting strategies exist to manage the percutaneous tract opening, including placement of an external nephrostomy tube, placement of an internal ureteral stent, or no external or internal tube. The decision to place or not place a tube is handled differently among clinicians and may affect patient outcomes. Objectives: To assess the effects of tubeless PNL (with ureteral stenting), totally tubeless PNL (without ureteral stenting or nephrostomy), and standard PNL (nephrostomy only) for the treatment of kidney stones in adults. Search methods: We performed a systematic literature search in multiple biomedical databases (CENTRAL, MEDLINE, Embase, Web of Science), as well as in two clinical trial registries. We also handsearched reference lists of relevant publications and conference proceedings. We applied no language restrictions. The latest search update was conducted in September 2022. Selection criteria: We included randomized controlled and quasi-randomized controlled trials of adult patients who received tubeless, totally tubeless, or standard PNL for treating kidney stones. We defined tubeless PNL as no nephrostomy tube, but ureteral stenting, while totally tubeless PNL meant no nephrostomy tube or ureteral stenting. Both interventions were compared to standard PNL with placement of a nephrostomy tube (only). We considered access tubes of any sizes. We only considered unilateral PNL with single-tract access. There were no exclusions on stone composition, size, or location. Data collection and analysis: Two review authors independently screened the literature, extracted data, assessed risk of bias, and rated the certainty of evidence using GRADE. Primary outcomes were severe adverse events and postoperative pain, and secondary outcomes were operating time, length of hospital stay, and stone-free rate. We used the random-effects model for meta-analysis. Main results: We included 10 studies in the review. Participant age varied among studies, ranging from 20 to 60 years. Detailed information on stone characteristics was rarely presented. Tubeless PNL versus standard PNL. We are very uncertain whether there is a difference in severe adverse events (SAEs) between tubeless PNL and standard PNL (risk ratio (RR) 1.53, 95% confidence interval (CI) 0.14 to 16.46; I2 = 42%; 2 studies, 46 participants; very low-certainty evidence). Tubeless PNL may have little to no effect on pain on postoperative day one (mean difference (MD) 0.56 lower, 95% CI 1.34 lower to 0.21 higher; I2 = 84%; 4 studies, 186 participants; low-certainty evidence), and probably results in little to no difference in operating room time (MD 0.40 longer (in minutes), 95% CI 4.82 shorter to 5.62 longer; I2 = 0%; 3 studies, 81 participants; moderate-certainty evidence). Tubeless PNL may reduce length of hospital stay (MD 0.90 shorter, 95% CI 1.45 shorter to 0.35 shorter; I2 = 84%; 6 studies, 238 participants; low-certainty evidence). We are very uncertain of the effect of tubeless PNL on blood transfusions (RR 0.64, 95% CI 0.16 to 2.52; I2 = 0%; 4 studies, 161 participants; very low-certainty evidence), sepsis or fever (RR 0.50, 95% CI 0.05 to 4.75; I2 = not applicable; 2 studies, 82 participants; very low-certainty evidence), or readmissions (RR 1.00, 95% CI 0.07 to 14.21; I2 = not applicable, 1 study, 24 participants; very low-certainty evidence). Totally tubeless versus standard PNL. Totally tubeless PNL may result in lower SAE rates (RR 0.49, 95% CI 0.19 to 1.25; I2 = 0%; 2 studies, 174 participants; low-certainty evidence) and pain on postoperative day one (MD 3.60 lower, 95% CI 4.24 lower to 2.96 lower; I2 = Not applicable; 1 study, 50 participants; low-certainty evidence). Totally tubeless PNL may result in little to no difference in operating room time (MD 6.23 shorter (in minutes), 95% CI 14.29 shorter to 1.84 longer; I2 = 72%; 2 studies, 174 participants; moderate-certainty evidence) and sepsis or fever (RR 0.33, 95% CI 0.01 to 7.97; I2 = not applicable; 1 study, 90 participants; low-certainty evidence). Totally tubeless PNL likely shortens the length of hospital stay (MD 1.55 shorter, 95% CI 1.82 shorter to 1.29 shorter; I2 = 0%; 4 studies, 274 participants; moderate-certainty evidence). We are very uncertain of the effect of totally tubeless PNL on blood transfusions (RR 0.62, 95% CI 0.26 to 1.48; I2 = 0%; 4 studies, 274 participants; very low-certainty evidence) or readmissions (RR not estimable, 95% CI not estimable; I2 = not applicable; 1 study, 50 participants; very low-certainty evidence). We found no studies comparing tubeless mini versus standard mini-PNL or totally tubeless mini versus standard mini-PNL. Authors' conclusions: When comparing tubeless to standard PNL with regard to the predefined primary outcomes of this review, there may be little difference in early postoperative pain, while we are very uncertain of the effect on SAEs. People treated with tubeless PNL may benefit from a reduced length of stay compared to standard PNL. When comparing totally tubeless to standard PNL, early postoperative pain and severe adverse events may be reduced with totally tubeless PNL. The certainty of evidence by outcome was mostly very low (range: moderate to very low) for the comparison of tubeless to standard PNL and low (range: moderate to very low) for the comparison of totally tubeless to standard PNL. The most common reasons for downgrading the certainty of the evidence were study limitations, inconsistency, and imprecision. We did not find randomized trial evidence for other comparisons. Overall, further and higher-quality studies are needed to inform clinical practice.
CRIS-Team Scopus Importer:2023-08-11